Systematic underestimation of the epigenetic clock and age acceleration in older subjects - Louis Y. El Khoury; Tyler Gorrie-Stone; Melissa Smart; Amanda Hughes; Yanchun Bao; Alexandria Andrayas; Joe Burrage; Eilis Hannon; Meena Kumari; Jonathan Mill; Leonard C. Schalkwyk (Genome Biology, 2019)
Abstract Background The Horvath epigenetic clock is widely used. It predicts age quite well from 353 CpG sites in the DNA methylation profile in unknown samples and has been used to calculate “age acceleration” in various tissues and environments. Results The model systematically underestimates age in tissues from older people. This is seen in all examined tissues but most strongly in the cerebellum and is consistently observed in multiple datasets. Age acceleration is thus age-dependent, and this can lead to spurious associations. The current literature includes examples of association tests with age acceleration calculated in a wide variety of ways. Conclusions The concept of an epigenetic clock is compelling, but caution should be taken in interpreting associations with age acceleration. Association tests of age acceleration should include age as a covariate.